A "Clickable" MTX Reagent as a Practical Tool for Profiling Small‐Molecule–Intracellular Target Interactions via MASPIT. Issue 3 (22nd January 2013) - Risseeuw, Martijn D. P.; De Clercq, Dries J. H.; Lievens, Sam; Hillaert, Ulrik; Sinnaeve, Davy; Van den Broeck, Freya; Martins, José C.; Tavernier, Jan; Van Calenbergh, Serge
Abstract We present a scalable synthesis of a versatile MTX reagent with an azide ligation handle that allows rapid γ‐selective conjugation to yield MTX fusion compounds (MFCs) appropriate for MASPIT, a three‐hybrid system that enables the identification of mammalian cytosolic proteins that interact with a small molecule of interest. We selected three structurally diverse pharmacologically active compounds (tamoxifen, reversine, and FK506) as model baits. After acetylene functionalization of these baits, MFCs were synthesized via a CuAAC reaction, demonstrating the general applicability of the MTX reagent. In analytical mode, MASPIT was able to give concentration‐dependent reporter signals for the established target proteins. Furthermore, we demonstrate that the sensitivity obtained with the new MTX reagent was significantly stronger than that of a previously used non‐regiomeric conjugate mixture. Finally, the FK506 MFC was explored in a cellular array screen for targets of FK506. Out of a pilot collection of nearly 2000 full‐length human ORF preys, FKBP12, the established target of FK506, emerged as the prey protein that gave the highest increase in luciferase activity. This indicates that our newly developed synthetic strategy for the straightforward generation of MFCs is a promising asset to uncover new intracellular targets using MASPIT cellular array screening.